Guerreiro - Machado reaction . Study in 1010 people from various departments of Peru - Cubas, Edgardo (1965)
He has practiced Guerreiro - Machado reaction in 1010 specimens from the same number of people , following the technique of 50% hemolysis of antigen using Bozicevich and total aqueous extract of T. cruzi ( forms of culture in medium Senekjie ) prepared Peruvian strains isolated from people and Trialoma infestans. In the study group , 551 Lima residents who had long previous residence in another department and 459 residents Samegua and Moquegua, locations known for their high endemicity for Chagas included . Reactions in 1010 , he found , 98 ( 9.70 %) were positive , 20 ( 1.98 %) suspicious and 31 ( 3.07 %) anticomplementary . The incidence was higher in females , 12.33 '% , and in the following age groups: 60 and older, 24.42 % ; 50 to 59 years , 13.86 % ; 40 to 49, 13.64 '% and 30 to 39, 9.16 % positive cases . De Lima 551 residents , 34 ( 6.17 % ) presented positive serology ; 1 ( 0.18 %) , suspicious and 7 ( 1.27 %) , anticomplementary . In 15 of the 34 positive subjects , xenodiagnosis was performed , resulting 7 positive . RFC 459 residents conducted in the department of Moquegua, was obtained , 64 (13.94 %) were positive , 19 ( 4.14 %) suspicious and 24 ( 5.23 %) anticomplementary . In this group RFC , 448 xenodiagnosis was performed the same number of people , finding 29 positive ( 6.47 %). Among the 34 positive residents of Lima , 6 had had several years of previous residence in chagasic areas of the department of Arequipa , 10 Moquegua, 8 in Tacna, 4 in San Martin, 2 in Cajamarca, 2 in Loreto, 1 in La Libertad and 1 in Iquique ( Chile) . More than 50% of the 1010 subjects studied were referred by clinical specialists , having considered Chagas disease among its diagnostic possibilities . Of the 98 positive cases reported in this study , 95 have been reported in previous publications (16, 20, 32 , 33) And three first reported . The three new cases , subjects are residents of Lima, one of them had had previous residency chogásicas areas of Arequipa, Moquegua in the second and third in San Martin. It is hoped that in the future ; diagnostic methods in uniformen surveys for the presence of American Trypanosomiasis , and thus determine the incidence of this disease in our country.